Life-cycle inequality: The black and white differential - Giacomo De Giorgi; Luca Gambetti; Costanza Naguib (University of Bern, Department of Economics, 2023)
With 20 years of PSID data, we document persistent racial differentials in life-cycle consumption dynamics. Starting from similar positions in the consumption distribution Blacks end up in lower percentiles than Whites. Education, income, and wealth are three key drivers of these different dynamics. Blacks tend to save less, and hence have less buffer than the Whites to prevent them from falling in the lower part of the consumption distribution.
Keywords: E21; D12; C3; 330; Consumption; Income; Savings; Inequality; Persistence; Life-Cycle